2017
DOI: 10.1371/journal.pone.0178611
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides use and the risk and mortality of cancer; systematic review and meta-analysis of observational studies

Abstract: BackgroundCardiac glycosides (CGs) including digitalis, digoxin and digitoxin are used in the treatment of congestive heart failure and atrial fibrillation.Pre-clinical studies have investigated the anti-neoplastic properties of CGs since 1960s. Epidemiological studies concerning the association between CGs use and cancer risk yielded inconsistent results. We have performed a systematic review and meta-analysis to summarize the effects of CGs on cancer risk and mortality.MethodsPubMed, Scopus, Cochrane library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 85 publications
(84 reference statements)
1
28
0
Order By: Relevance
“…In other words, efficacious concentrations cannot be obtained in the tumor without considerable toxicity in the patient. Due to the structural similarity to estrogen, several studies have suggested that digoxin may actually increase the risk for estrogen receptor positive breast cancer [62,63]. Based on these findings, we hypothesized that digoxin may be a good candidate at lower doses in combinatorial therapies for TNBC patients.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, efficacious concentrations cannot be obtained in the tumor without considerable toxicity in the patient. Due to the structural similarity to estrogen, several studies have suggested that digoxin may actually increase the risk for estrogen receptor positive breast cancer [62,63]. Based on these findings, we hypothesized that digoxin may be a good candidate at lower doses in combinatorial therapies for TNBC patients.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies indicate that digoxin use is not significantly associated with cancer incidence or cancer-specific mortality in a number of malignancies [ 18 21 ]. In contrast, other human studies suggest that digoxin could modify cancer initiation or progression in certain tissue types [ 22 24 ]. Potential effects of digoxin treatment on NMTC development, progression and treatment response have not been studied so far.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, also promising is the fact that a lower incidence in some types of cancer in patients on CG therapy (cardiac conditions) has been reported [ 4 ]. While another study claims the opposite [ 5 ], others stand somewhere in between [ 6 , 7 ]. However, what is quite certain and makes CGs a new hope for cancer treatment are clinical data showing that CGs, mainly digoxin, significantly prolong the survival of cancer patients otherwise treated with traditional chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%